Immobilization techniques improve volumetric hydrogen productivity of Caldicellulosiruptor species in a modified continuous stirred tank reactor - Thitiwut Vongkampang; Krishnan Sreenivas; Carl Grey; Ed W. J. van Niel (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Background Co-cultures and cell immobilization have been used for retaining biomass in a bioreactor, with the aim to improve the volumetric hydrogen productivity (QH2). Caldicellulosiruptor kronotskyensis is a strong cellulolytic species that possesses tāpirin proteins for attaching on lignocellulosic materials. C. owensensis has its reputation as a biofilm former. It was investigated whether continuous co-cultures of these two species with different types of carriers can improve the QH2. Results QH2 up to 30 ± 0.2 mmol L−1 h−1 was obtained during pure culture of C. kronotskyensis with combined acrylic fibres and chitosan. In addition, the yield of hydrogen was 2.95 ± 0.1 mol H2 mol−1 sugars at a dilution rate (D) of 0.3 h−1. However, the second-best QH2 26.4 ± 1.9 mmol L−1 h−1 and 25.4 ± 0.6 mmol L−1 h−1 were obtained with a co-culture of C. kronotskyensis and C. owensensis with acrylic fibres only and a pure culture of C. kronotskyensis with acrylic fibres, respectively. Interestingly, the population dynamics revealed that C. kronotskyensis was the dominant species in the biofilm fraction, whereas C. owensensis was the dominant species in the planktonic phase. The highest amount of c-di-GMP (260 ± 27.3 µM at a D of 0.2 h−1) were found with the co-culture of C. kronotskyensis and C. owensensis without a carrier. This could be due to Caldicellulosiruptor producing c-di-GMP as a second messenger for regulation of the biofilms under the high dilution rate (D) to prevent washout. Conclusions The cell immobilization strategy using a combination of carriers exhibited a promising approach to enhance the QH2. The QH2 obtained during the continuous culture of C. kronotskyensis with combined acrylic fibres and chitosan gave the highest QH2 among the pure culture and mixed cultures of Caldicellulosiruptor in the current study. Moreover, it was the highest QH2 among all cultures of Caldicellulosiruptor species studied so far.